The nematode fauna of the digestive tract of goats in the Moscow region - I. A. Pimenov; D. N. Kuznetsov; I. M. Odoevskaya; A. D. Afanasyev; A. I. Varlamova (Российский паразитологический журнал, 2023)
The purpose of the research is to study the fauna of gastrointestinal nematodes of goats in the Moscow region. Materials and methods. The studies were carried out from December 2022 to April 2023. The object for the studies was the contents of the digestive tracts of 10 goats from small farms in the Moscow region, which were collected and fixed according to the method of K. I. Skryabin (1928). The species of detected nematodes were identified according to V. M. Ivashkin et al. (1989). A study of fecal samples was carried out, the genus of infective larvae was determined by the method of P. A. Polyakov (1953). Results and discussion. Three species of nematodes were detected: Haemonchus contortus, Trichostrongylus colubriformis and Teladorsagia circumcincta according to the results of helminthological necropsies of goats. The highest rate of infection was noted for H. contortus and the highest intensity of infection was noted for T. colubriformis. The nematode T. circumcincta was found only in one of 10 studied goats, in the amount of 13 worms. The larvae of Trichostrongylus, Oesophagostomum and Chabertia genera were identified according to their morphology in the examined feces samples in one of the seven farms. Many larvae of the first two genera were found, and Сhabertia larvae were single. The low species diversity noted in this study may be due to the presence of anthelmintic-resistant nematode strains.